ANALISIS KONSISTENSI PERENCANAAN DAN PENGANGGARAN DI KABUPATEN TULUNGAGUNG (STUDI PADA BIDANG PENDIDIKAN DAN KESEHATAN TAHUN 2010-2012) - Solichah, Siti Imroatus; Khusaini, Moh. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Planning and budgeting is an integral process that important in the annual development, especially the development of fundamental sectors such as education and health. That complex process produces RKPD, PPAS and APBD. RKPD is a document that capture aspirations of local communities through â€œmusrenbangâ€. Furthermore, the work plan and funding RKPD used as guidelines in preparing PPAS and APBD later. PPAS bridge between planning (RKPD) with policy and the draft budget based on the availability of budget. APBD reflects the budget allocation to implement priority programs and activities that have been agreed in the document PPAS and became the basis for the implementation of regional financial year budget. This study aims to assess the consistency between the documents. The data used in this study is a secondary data, there are programs, activities and budget plan in the document RKPD, PPAS, and APBD Tulungagung 2010 to 2012. Consistency of programs and activities were analyzed using MKPP for linkage between RKPD and PPAS and between PPAS and APBD. While the budget consistency is analyzed with correlation. Furthermore, the authors also conducted interviews with the Regional Development Planning Board (Bappeda) to determine the cause of the inconsistency between the documents. During the period 2010 to 2012 in Tulungagung, still occurs inconsistency between RKPD and PPAS or between PPAS and APBD. Overall, higher consistency found between PPAS and APBD. Factors suspected to affect this because PPAS is a mutual agreement between the executive and parliament, so if there is a change in the budget is not too big, while RKPD is an only executive decision product. Keywords: Consistency, Planning and Budgeting, RKPD-PPAS, PPAS-APBD